The potential impacts of climate change on ex situ conservation options for recalcitrant-seeded species - Fernández, Ana; León-Lobos, Pedro; Contreras, Samuel; Ovalle, Juan F.; Sershen,; van der Walt, Karin; Ballesteros, Daniel (Frontiers in Forests and Global Change, 2023)
Recalcitrant seeds are characterized by desiccation and freezing sensitivity, and short storage longevity. These physiological attributes obviate their ex situ conservation in conventional seed banks, where seeds are stored dry at sub-zero temperatures (typically, 15% relative humidity and –20°C) for extended periods of time. Propagation of plants for field collections (e.g., botanical gardens, nurseries, and arboretums) is a valuable ex situ conservation option. However, these collections are relatively costly, require high maintenance, preserve limited genetic diversity and/or are directly exposed to biotic (e.g., pests) and abiotic (e.g., climatic) threats. Therefore, recalcitrant-seeded (RS) species are dependent on cryopreservation for their safe and long-term ex situ conservation. Different explant sources such as whole seeds, zygotic embryos, dormant buds, shoot tips, and pollen, can be used for plant propagation of RS species in field collections as well as for their cryopreservation. The success of the propagation or the cryopreservation of these explants often depends on their developmental status, vigor, and/or tolerance to desiccation and chilling/freezing. These attributes are modulated by the environment where the donor plant grows and we hypothesize that climate change, by affecting these biological attributes, would impact the success of explant propagation and cryopreservation. To support this hypothesis, we have reviewed how temperature changes and drought, the two main climate change scenarios, affect the main biological attributes that are directly involved in the success of ex situ conservation of tropical and temperate RS species. In general, increases in temperature and drought will negatively affect plant development in field collections and the quality of the explants used in cryopreservation. Consequently, field collections of RS species may need to be moved to more suitable places (e.g., higher latitudes/altitudes). Additionally, we may find a reduction in the success of cryopreservation of RS species germplasm directly harvested from field collections. However, we cannot always generalize these effects for all species since they often depend on the origin of the species (e.g., tropical and temperate species tend to respond to climate change differently), the genotype, the adaptive genetic potential of each population, and the severity of the environmental change. On the other hand, the increase in temperatures and water stress in donor plants at high-latitude areas and also some tropical environments may favor the production of seeds and seedlings better adapted to drying, and hence, increase the success of plant propagation and zygotic embryo cryopreservation.